Anjouan (Comores), un nœud dans les réseaux de l’océan Indien. Émergence et rôle d’une société urbaine lettrée et marchande (XVIIe-XXe siècle) - Sophie Blanchy (Afriques, 2015)
This article discusses the specific role played by the makabaila of Ndzuwani Island (Comoro archipelago) in trade routes across the Indian Ocean. Townspeople of Ndzuwani Island, the makabaila were learned merchants and landowners with their origin in the Bâ ‘Alawî sharif clan from Hadhramawt. Established on the Swahili coast since the sixteenth century and in the Comoros at the end of this century, these sharifs developed intensive commercial links between Hadhramawt, the Lamu archipelago, and the Comoros. Several factors helped the makabaila make the island a commercial hub, including logistical maritime access and development of towns, which were both economic and intellectual centres producing elite ideology. Unlike that of other Comorian people, the makabaila ethos was linked not to territory but to networks. The subsequent French colonisation of this island at the end of the nineteenth century did not prevent the makabaila from retaining their dominant status. Key to this was the monopoly they fostered on education. In the twentieth century, Ndzuwani became one of the largest suppliers of aromatic plants in the world. When independence arrived, the makabaila controlled this exportation, which was essential in maintaining social stratification and power.